2015
DOI: 10.1088/1367-2630/17/7/072002
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of oscillations in two-dimensional spectra of excitonically-coupled molecular systems

Abstract: We investigate an artificial molecular dimer made of two dipole coupled cyanine dye monomers in which a strong coherent coupling between electronic and vibrational degrees of freedom arises. Clear signatures of this coupling are reflected in an oscillatory time evolution of the off-diagonal vibronic cross peaks in the two-dimensional optical photon echo spectrum. We find a strong coherence component damped by fast electronic dephasing ( 50 ≈ fs) accompanied by a much weaker component which decays on the longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 48 publications
7
72
2
Order By: Relevance
“…In conclusion, we have shown that, under ambient physical conditions, it is irrelevant for the life- Even under (unrealistically) weak electronic dephasing, the electronic coherence lifetime is not enhanced by the vibronic components. The same conclusion has been drawn from the study of indocarbocyanine dye molecules 33 . In addition, we find that a strong mixing of electronic and anticorrelated vibrational components of the wavefunction due to strong vibronic coupling does not enhance the vibrational amplitude at long times under ambient conditions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In conclusion, we have shown that, under ambient physical conditions, it is irrelevant for the life- Even under (unrealistically) weak electronic dephasing, the electronic coherence lifetime is not enhanced by the vibronic components. The same conclusion has been drawn from the study of indocarbocyanine dye molecules 33 . In addition, we find that a strong mixing of electronic and anticorrelated vibrational components of the wavefunction due to strong vibronic coupling does not enhance the vibrational amplitude at long times under ambient conditions.…”
Section: Discussionsupporting
confidence: 76%
“…In addition to the electronic coherence, signatures of the vibrational coherence of the pigmentprotein host can also be accessed on the same spectroscopic footing [26][27][28][29] . Yet, electronic coherence can be distinguished from vibrational coherence 30,33,34 . Long-lived pure electronic coherence is unexpected to exist in most light harvesting complexes.…”
mentioning
confidence: 99%
“…An additional strong coupling of the excitonic to the nuclear degrees of freedom was also considered (31-39) as a possible driving source of coherence. Such a mechanism can yield longer-lived oscillations of the cross-peak amplitude (40,41), yet, a strong vibronic coupling is required, and the oscillation amplitudes typically remain small. Moreover, in general, electronic coherence could only be enhanced by vibrational coherence if it lives at least as long It is used as a consistence check for the electronic dephasing time.…”
Section: Significancementioning
confidence: 99%
“…A long-standing problem in molecular spectroscopy is to understand the roles of nuclear vibrations in the electronic structure of interacting molecules (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Since the early work of Förster, Kasha, Fulton and Gouterman (2,(14)(15)(16), it has been recognized that the absorption spectra of interacting molecules can appear strikingly different than that of the constituent monomers, particularly when the monomer spectrum exhibits a pronounced vibronic progression, which is due to the coupling between electronic and vibrational motion (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%